2021
DOI: 10.1186/s13102-021-00237-9
|View full text |Cite
|
Sign up to set email alerts
|

Development of new 9-ball test protocols for assessing expertise in cue sports

Abstract: Background This study aimed to develop new test protocols for evaluating 9-ball expertise levels in cue sports players. Methods Thirty-one male 9-ball players at different playing levels were recruited (recreational group, n = 8; university team, n = 15; national team, n = 8). A 15-ball test was administered to indicate overall performance by counting the number of balls potted. Five skill tests (power control, cue alignment, angle, back spin, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…After each break shot, the positions of all balls remaining on the pool table were digitized manually ( Figure 1 ). Firstly, the “perspective grid” was applied to calibrate the pool table and was set as 127 cm × 254 cm ( Pan et al, 2021 ) which was the dimension of a standardized pool table used in professional tournaments. Then, the “mark” tool was implemented to mark each of the ball remained on the table.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After each break shot, the positions of all balls remaining on the pool table were digitized manually ( Figure 1 ). Firstly, the “perspective grid” was applied to calibrate the pool table and was set as 127 cm × 254 cm ( Pan et al, 2021 ) which was the dimension of a standardized pool table used in professional tournaments. Then, the “mark” tool was implemented to mark each of the ball remained on the table.…”
Section: Methodsmentioning
confidence: 99%
“…Top-view videos of professional 9-ball tournaments were downloaded and analyzed using Kinovea (version 0.8.27, available for download at: http://www.kinovea.org), a 2D motion analysis software which has shown good accuracy in measuring objects at an angle range of 45 • to 90 • (Puig- Diví et al, 2019). In a previous study on 9-ball test protocols, excellent inter-and intra-rater reliability was found in measuring ball movements from video recordings using Kinovea (Pan et al, 2021). After each break shot, the positions of all balls remaining on the pool table were digitized manually (Figure 1).…”
Section: Data Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the successes in making an accurate shot in billiards is power control [14]. With good power control, an athlete will be able to perform an accurate hitting technique as expected [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…One of the successes in making an accurate shot in billiards is power control [14]. With good power control, an athlete will be able to perform an accurate hitting technique as expected [14,15]. The factors that determine the accuracy of shots in billiards are examined in relation to the physical condition components which include arm muscle strength, back muscle strength, and leg muscle strength.…”
Section: Introductionmentioning
confidence: 99%